2015
DOI: 10.1590/1677-3225v14n1a03
|View full text |Cite
|
Sign up to set email alerts
|

Civil liability related to imaging exams in Brazil

Abstract: Aim: To analyze all court lawsuits in Brazil in relation to civil liability involving radiographic and tomographic images up to February 2014. Methods: All Brazilian courts were surveyed for "civil liability," "error," "radiology," "radiography," and "tomography," returning 3923 second-instance lawsuits. Out of them were excluded labor legislation, health insurance coverage of radiological examinations, and criminal liability cases and 359 were selected. Compliance with expert reports, involvement of imaging e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Similar litigation cases are noted internationally, where inadequate prescription of diagnostic imaging in areas such as oral surgery, implant placement and orthodontic treatment was claimed to have contributed to harm. 75,76 The above-mentioned evidence supports strongly the correct use of radiographic examinations by dental practitioners wherever relevant and applicable. In a report by Brown and Monsour, 5 there is some evidence indicating that within the field of invasive oral surgery, there has been a preference of CBCT to PR among Australian practitioners in recent years.…”
Section: Legal Aspects Of Panoramic Radiography and Cone Beam Computementioning
confidence: 70%
See 1 more Smart Citation
“…Similar litigation cases are noted internationally, where inadequate prescription of diagnostic imaging in areas such as oral surgery, implant placement and orthodontic treatment was claimed to have contributed to harm. 75,76 The above-mentioned evidence supports strongly the correct use of radiographic examinations by dental practitioners wherever relevant and applicable. In a report by Brown and Monsour, 5 there is some evidence indicating that within the field of invasive oral surgery, there has been a preference of CBCT to PR among Australian practitioners in recent years.…”
Section: Legal Aspects Of Panoramic Radiography and Cone Beam Computementioning
confidence: 70%
“…76,78 Overseas studies have reported misdiagnosis as being responsible for the majority of litigation cases involving radiologists. 75 Incidental radiographic findings for the dento-maxillofacial region have shown as high as 93.42% for non-dental pathology. 79 However, there is generally a lack of consistency in the literature accounting for incidental findings, largely due to different study designs used.…”
Section: Legal Aspects Of Panoramic Radiography and Cone Beam Computementioning
confidence: 99%